Validation and Implementation of 4-domain Patient-reported Outcome Measures (PROMs) Tailored for Orthopedic Sports Medicine - Piedade, Sérgio Rocha; Hutchinson, Mark R.; Ferreira, Daniel Miranda; Ferretti, Mario; Maffulli, Nicola (International Journal of Sports Medicine, 2021)
The validation of a 4-domain PROM tailored to orthopedic sports medicine was performed through item generation, item scaling, validity and reliability testing, statistical analysis, as well as item reduction. Conbrach's alpha was used to verify item homogeneity, i. e. their accuracy or consistency. This PROM showed acceptable statistical accuracy and clinical applicability for a variety of surgical treatments, regardless of the anatomical injury sites. Moreover, this PROM considers the athletes’ primary physical demands in an non-injured baseline condition, their motivation to continue sports practice and participation, and the influence of sports practice on their quality of life. This 4-domain PROM tailored for orthopedic sports medicine appears to be a valid tool to assess athletes and high-performing practitioners with sports injuries, recording their perception of injury, expectations of treatment; evaluation of postoperative care and treatment received, and perceived outcomes compared to their pre-injury status of physical demands in sports activity. The tool is unique, allowing direct comparisons between athletes’ perception of pre-injury baseline, injury, treatment, and outcome. It will be a welcome adjunct to the sports medicine professional’s tool box when assessing athlete’s status and outcome after injury and intervention.
Keywords: outcome studies; sports medicine